The Bahamas : Financial Sector Assessment Program-Technical Note on Financial Inclusion, Retail Payments, and SME Finance. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2019)
The CBOB considers increased financial inclusion as a critical reform area. In this regard, the FSAP assessed developments in financial inclusion for individuals and enterprises (SME finance), retail payments and provides recommendations for improvements. A review of the market was undertaken using the Payment Aspects of Financial Inclusion (PAFI) framework covering areas such as the legal/regulatory framework and oversight, retail payment systems and instruments, access to transaction accounts and use cases, as well as SME policy, credit infrastructure, economic empowerment funds and consumer protection and financial literacy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet